Asymmetric frequency shift in advertisement calls of sympatric frogs - Jansen, Martin; Plath, Martin; Brusquetti, Francisco [UNESP]; Ryan, Michael Joseph (De Gruyter, 2016)
Character displacement is commonly observed when species occur in secondary contact zones and traits related to resource competition or reproduction diverge in sympatry. However, few studies have considered the factors determining and delimiting the direction of character evolution in this context. We studied displacement in advertisement calls in two species of hylid frogs from allopatric and sympatric populations, both of which call with similar frequencies but differ substantially in temporal parameters. We found asymmetrical character displacement in sympatry, as only Scinax madeirae (but not S. fuscomarginatus) repeatedly showed displacement. Instead of diverging in already existing differences in temporal characters, S. madeirae showed character displacement for frequency-related characters. We explored possible reasons for this specific pattern concerning the displaced characters and tested if socio-functional constraints in specific call parameters are responsible for the shift of only spectral parameters in that species. Finally, we argue that the simultaneous action of ecological and reproductive character displacement, or alternatively, a short-term behavioral response for the same reason (avoidance of hybridization) could explain the pattern. The present study identifies a set of new hypotheses that will stimulate future research on mechanisms of mate recognition and behavioral responses.
Keywords: Ecological character displacement; Mating call variation; Reproductive character displacement; Scinax fuscomarginatus; Scinax madeirae